Plasma Membrane MCC/Eisosome Domains Promote Stress Resistance in Fungi - Lanze, Carla E. (Microbiol Mol Biol Rev, 2020)
There is growing appreciation that the plasma membrane orchestrates a diverse array of functions by segregating different activities into specialized domains that vary in size, stability, and composition. Studies with the budding yeast Saccharomyces cerevisiae have identified a novel type of plasma membrane domain known as the MCC (membrane compartment of Can1)/eisosomes that correspond to stable furrows in the plasma membrane. MCC/eisosomes maintain proteins at the cell surface, such as nutrient transporters like the Can1 arginine symporter, by protecting them from endocytosis and degradation. Recent studies from several fungal species are now revealing new functional roles for MCC/eisosomes that enable cells to respond to a wide range of stressors, including changes in membrane tension, nutrition, cell wall integrity, oxidation, and copper toxicity. The different MCC/eisosome functions are often intertwined through the roles of these domains in lipid homeostasis, which is important for proper plasma membrane architecture and cell signaling. Therefore, this review will emphasize the emerging models that explain how MCC/eisosomes act as hubs to coordinate cellular responses to stress. The importance of MCC/eisosomes is underscored by their roles in virulence for fungal pathogens of plants, animals, and humans, which also highlights the potential of these domains to act as novel therapeutic targets.